Additive Manufacturing in Healthcare - Marisela Rodríguez-Salvador; Leonardo Azael Garcia-Garcia (Foresight and STI Governance)
The presence of additive manufacturing (AM), in particular 3D printing, is relatively young, but dynamic field that is changing the face of many sectors. Additive production technologies provide wide opportunities for the creation of complex and personalized products and the reduction of time, labor, and other expenses. This paper will focus on AM in healthcare and identify the main areas for its application and the most popular materials. The period under analysis is from January 2005 to April 2015. The analysis involved an iterative search to establish the best queries for retrieving data and a patent analysis. The obtained results were assessed by experts in the field. Through this research, three main applications were identified with dental prosthetics being the most prolific. A wide range of materials were identified, where plastics predominate. Polyethylene was most frequently patented for vascular grafts and tendon replacements, while ceramics were found to be the most useful material for dental applications. Only a few patents disclosed the use of metals, titanium being the most prevalent. This research provides valuable insights for the advancement of additive manufacturing in healthcare applications.